Auditoría financiera a la Junta Parroquial de Pucayacu del cantón La Maná período 2011-2012 - Guerra Moreno, Lizandra Pamela (2013)
The research was carried out in order to run a financial audit to the vestry of La Maná canton Pucayacu 2011-2012 period located in the Eliseo Ibáñez Street between Emeraldas and Brazil La Maná canton province of Cotopaxi. The methodological procedure used for the audit consists of three phases of the process: phase I, planning which is divided into preliminary and specific; the preliminary, configured in a preliminary strategy to follow on the work, based on the accumulated knowledge and information obtained from the entity to be audited; Specific, defined the strategy through the determination of specific procedures to apply for each component and the way in which work will be developed in the following phases; Phase II implementation, starts with the implementation of the specific programs produced in the previous phase, continues with the gathering of information, the verification of the financial results, identification of the findings, the conclusions of major components and communication to administration of the entity to resolve problems and promote efficiency and effectiveness in its operations. In this phase, approximately 60% of the estimated time was used to run the audit, which was divided into 50% to develop findings and conclusions and 10% for the results in the review process, applied techniques such as observation, selective review, comparison, investigation and analysis, prepared the respective roles of work, leaves of significant findings; Phase III communication of results, prepared the opinion of the auditor and the draft of the report with the results obtained at the conclusion of the audit, which were communicated to the highest authority of the entity